Bound on Hankel Determinants H(2)4 (F) and H(3)4 (F) for Lemniscate Starlike Functions - Kumar, Sushil; Rai, Pratima; ÇETİNKAYA, ASENA (Honam Mathematical Soc., 2023)
We determine the upper bounds on fourth order Hankel de-terminants H4(2) (f) and H(3) 4 (f) for the class S*L of lemniscate starlike functions defined on the open unit disk which was introduced by Sok ' o l and Stankiewicz in [17].
Bound on Hankel Determinants H(2) for Lemniscate Starlike Functions
Keywords: Starlike Functions; Lemniscate Starlike Function; Coefficient Estimates; Third and Fourth Order Hankel Determinants